Pengaruh Konsumsi Fast Food terhadap Risiko Obesitas pada Remaja Perkotaan - Sarah Lina Muzakiyyah Pramana; Andriyani Andriyani; Nurmalia Lusida (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2025)
Obesity is a pressing health issue in Indonesia, especially among adolescents in urban areas. This study aims to analyze the impact of fast food consumption on obesity risk. The method used was a literature review by analyzing 15 relevant literatures using journals published in the last 5 years through Google Scholar and PubMed databases. This research was conducted from March 2025 to April 2025. The results showed that consumption of fast food, which is rich in calories and low in fiber, has a significant association with an increased risk of obesity in adolescents. Adolescents in urban areas consume fast food more frequently compared to those in rural areas, which contributes to health problems. The main conclusion of this study is the need for the development of nutrition education programs as well as the implementation of government policies to encourage healthy eating and increase physical activity levels among adolescents. Keywords: , ,